Ectopic Expression of SjCBL1, Calcineurin B-Like 1 Gene From Sedirea japonica, Rescues the Salt and Osmotic Stress Hypersensitivity in Arabidopsis cbl1 Mutant - Cho, Joo Hyuk; Choi, Mi Na; Yoon, Kwan Hee; Kim, Kyung-Nam (Frontiers in Plant Science, 2018)
Extensive studies with Arabidopsis thaliana suggested that calcineurin B-like (CBL) proteins constitute a unique family of calcium sensors in plants, which mediate a variety of abiotic stress responses. However, little is known about their function in most plants that do not have available genome sequences. In this study, we have developed a pair of universal primers that make it possible to isolate CBL1-like genes from various plants without sequence information. Using these primers, we successfully cloned a full-length cDNA of CBL1-like gene in Sedirea japonica (SjCBL1). Bimolecular fluorescence complementation (BiFC) and pull-down assays demonstrated that like Arabidopsis CBL1 (AtCBL1), SjCBL1 can interacts physically with Arabidopsis CBL-interacting protein kinase 1 (AtCIPK1) at the plasma membrane of plant cells in a Ca2+-dependent manner. In addition, overexpression of SjCBL1 in the Arabidopsis cbl1 mutant resulted in not only rescuing the hypersensitive phenotype toward salt and osmotic stresses, but also substantially enhancing the tolerance to them. Taken together, these results strongly suggest that SjCBL1 is a functional ortholog of AtCBL1 in Sedirea japonica, which can play a critical role in response to salt and osmotic stresses. Therefore, it is clear that our findings should significantly contribute to broadening and deepening our understanding of the CBL1-mediated Ca2+ signaling networks in the plant kingdom.